Clinical implications of somatic allele expansion in female FMR1 premutation carriers - Aishworiya, Ramkumar; Hwang, Ye Hyun; Santos, Ellery; Hayward, Bruce; Usdin, Karen; Durbin-Johnson, Blythe; Hagerman, Randi; Tassone, Flora (Scientific reports, 2023)
Carriers of a premutation allele (PM) in the FMR1 gene are at risk of developing a number of Fragile X premutation asssociated disorders (FXPAC), including Fragile X-associated Tremor/Ataxia Syndrome (FXTAS), Fragile X-associated Primary Ovarian Insufficiency (FXPOI), and Fragile X-associated neuropsychiatric disorders (FXAND). We have recently reported somatic CGG allele expansion in female PM; however, its clinical significance remains unclear. The aim of this study was to examine the potential clinical association between somatic FMR1 allele instability and PM associated disorders. Participants comprised of 424 female PM carriers age 0.3– 90 years. FMR1 molecular measures and clinical information on the presence of medical conditions, were determined for all subjects for primary analysis. Two sub-groups of participants (age ≥ 25, N = 377 and age ≥ 50, N = 134) were used in the analysis related to presence of FXPOI and FXTAS, respectively. Among all participants (N = 424), the degree of instability (expansion) was significantly higher (median 2.5 vs 2.0, P = 0.026) in participants with a diagnosis of attention deficit hyperactivity disorder (ADHD) compared to those without. FMR1 mRNA expression was significantly higher in subjects with any psychiatric disorder diagnosis ( P = 0.0017); specifically, in those with ADHD ( P = 0.009), and with depression ( P = 0.025). Somatic FMR1 expansion was associated with the presence of ADHD in female PM and FMR1 mRNA levels were associated with the presence of mental health disorders. The findings of our research are innovative as they suggest a potential role of the CGG expansion in the clinical phenotype of PM and may potentially guide clinical prognosis and management.